IMPROVED PREPAREDNESS COMMUNITIES IN FACING DISASTERS THROUGH DISASTER MITIGATION ON SAPEKEN ISLAND, SUMENEP REGENCY - Hariyono Hariyono (Frontiers in Community Service and Empowerment, 2022)
Disasters can happen anytime and anywhere. Living as an archipelagic community is an advantage as well as a risk for the people of Sapeken Island. Behind the natural beauty and richness of life, the community is far from education related to disaster mitigation, and even government data related to mapping regional vulnerabilities and capacities are not optimal. The community-based disaster mitigation education program on Sapeken Island organized by the Disaster Management Masters Program at Airlangga University in collaboration with the Ksatria Airlangga Floating Hospital aims to improve preparedness and increase community capacity in dealing with potential disasters that can occur on Sapeken Island. Based on the results of the pre-test and post-test conducted, the level of community knowledge about disaster mitigation tends to be low and has an average increase of 9% in the post-test knowledge of earthquakes and an average increase of 29% in tsunami knowledge. In addition to disaster mitigation education programs, the community is also invited to determine gathering points and evacuation routes as anticipation and preparedness in the event of an unwanted disaster while waiting for evacuation assistance to arrive. Disaster education programs for archipelagic communities are very important to increase community capacity in addition to developing their tourism potential. So that the community can develop in a balanced way in developing tourism potential in the islands by taking into account the elements of disaster risk that can be prevented or reduced.